Fused Triazole-Azepine Hybrids as Potential Non-Steroidal Antiinflammatory Agents - Sergii Demchenko; Roman Lesyk; Oleh Yadlovskyi; Serhii Holota; Sergii Yarmoluk; Sergii Tsyhankov; Anatolii Demchenko (MDPI AG, 2023)
Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the oldest and most widely used groups of drugs nowadays. However, the problem of searching for and creating new NSAIDs remains open, primarily due to the risks owing to their short- and long-term use. In this context, triazole-azepine hybrid molecules are attractive and prospective objects for the rational design of novel potential NSAIDs. In the present work studies of 3-aryl-6,7,8,9-tetrahydro-5H-[1,2,4]triazolo[4,3-a]azepines as potential non-steroidal anti-inflammatory agents are reported. Evaluation of drug-like properties for all tested triazole-azepine hybrids was performed in silico using SwissADME. The screening of analgesic and anti-inflammatory activities was performed in vivo using acid-induced writhing and carrageenin-induced hind paw oedema models in mice. Derivatives with activity levels more potent compared with reference drugs ketorolac and diclofenac sodium were identified. Preliminary SAR was performed based on the screening results.